Teachers' use of technology: examining the domains of laptop competence - Moses, Priscilla; Wong, Su Luan (Institute for Computer Sciences, Social Informatics and Telecommunications Engineering (I C S T), 2021)
Introduction: The current coronavirus pandemic has forced the transition from face-to-face teaching and learning to fully online in Malaysia. Objectives: To examine the domains of laptop competence and its relationship with laptop use among teachers. Methods: A quantitative descriptive survey design using questionnaires involved 133 Mathematics and Science secondary school teachers. Results: Based on the results, the teachers are highly competent in word processor; basic laptop operation skills; telecommunication; spreadsheet; multimedia integration; and setup, maintenance, and troubleshooting of laptop but only moderately competent in media communication; and database. There was a significant positive relationship between teachers’ laptop competence and laptop use. Conclusion: Act as a guide to plan effectual training according to the needs of the teachers based on each item of the domains outlined to promote more rigorous use of laptops among the teachers.